Soil cement as a constructive material for anaerobic bioreactor corps - Karpushyn, Serhii (Academic journal Industrial Machine Building Civil Engineering, 2018)
One of the promising directions of modern alternative energy is anaerobic biotechnology for the production of biogas (so-called sewage gas). The main problem of hampering widespread use is biogas plants high cost. A new design of an anaerobic bioreactor for the production the biogas is proposed, where soil cement is used as a constructive material of continuous and monolithic construction of the corps bottom and walls. A structural and logical scheme for designing a bioreactor from soil cement for specific capacities of pig farms in geotechnical and climatic conditions has been developed and presented. Also the technological features of object construction by drilling and mixing technology are presented.